SWOBODA KORZYSTANIA Z MIEJSC PUBLICZNYCH NA PRZYKŁADZIE MORZA I WYBRZEŻA MORSKIEGO - Kamińska, Renata (Zeszyty Prawnicze, 2016)
FREEDOM TO USE PUBLIC PLACES AS EXEMPLIFIED BY THE USE OF THE SEA AND SEASHORE Summary In Roman law the sea and its shore were considered res communes omnium, common property. This classification gave rise to two important consequences. Firstly, everyone was granted the right to their free access and use, viz. fishing, hauling fishing nets in, mooring boats were all permitted in such places. Furthermore, it was also admissible to build a cottage or an adobe on the coast, and to acquire property rights to it. The second consequence of the recognition of the sea and shore as res communes omnium was that any interested party could be granted legal protection if his entitlements within this scope were violated. One of the legal measures available was actio iniuriarum, alongside injunctions. Protection by injunction was also provided forthe sea itself and the shore as such.